2021
DOI: 10.1186/s12985-021-01612-1
|View full text |Cite
|
Sign up to set email alerts
|

Plant responses to geminivirus infection: guardians of the plant immunity

Abstract: Background Geminiviruses are circular, single-stranded viruses responsible for enormous crop loss worldwide. Rapid expansion of geminivirus diversity outweighs the continuous effort to control its spread. Geminiviruses channelize the host cell machinery in their favour by manipulating the gene expression, cell signalling, protein turnover, and metabolic reprogramming of plants. As a response to viral infection, plants have evolved to deploy various strategies to subvert the virus invasion and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 214 publications
2
36
0
Order By: Relevance
“…The role of insect vectors, which is the key factor in the spread of begomoviruses, also contributes to their evolution ( Seal et al, 2006 ; Materatski et al, 2021 ). The adaptive response of co-evolution among viruses and insects is supported by the continual and circulative dispersal of the virus in the insect vector and the direct connection between begomoviruses and insects ( Nawaz-ul-Rehman and Fauquet, 2009 ; Gupta et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The role of insect vectors, which is the key factor in the spread of begomoviruses, also contributes to their evolution ( Seal et al, 2006 ; Materatski et al, 2021 ). The adaptive response of co-evolution among viruses and insects is supported by the continual and circulative dispersal of the virus in the insect vector and the direct connection between begomoviruses and insects ( Nawaz-ul-Rehman and Fauquet, 2009 ; Gupta et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, selecting targets within the viral genome is a crucial factor in conquering durable resistance. In this perspective, non-coding targets are more efficient over coding regions as they embed the key elements for virus replication and pathogenicity maintenance [77]. Furthermore, detecting the potential host factors involved in the resistance during plant-geminivirus interaction, multiplexed genetic engineering tools directing multiple targets, and targeted deletion in viral genomes can assist in developing disease-free plants and counteracting the emergence of CRISPR-resistant BGVs.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, it has been well demonstrated that host RNA-directed DNA methylation (RdDM)-mediated TGS is one of the most effective defense responses against geminiviruses due to their DNA replication in the host nucleus ( Raja et al, 2008 ; Zhong et al, 2017b ; Zarreen and Chakraborty, 2020 ; Gupta et al, 2021 ). In turn, geminiviruses evolve various VSRs to interfere with the host RdDM-mediated TGS ( Hanley-Bowdoin et al, 2013 ; Wang et al, 2019 ; Jin et al, 2021 ; Zhou, 2021 ).…”
Section: Discussionmentioning
confidence: 99%